HUBUNGAN HIGIENE PERORANGAN, SANITASI LINGKUNGAN DANRIWAYAT KONTAK DENGAN KEJADIAN SKABIES - ; Toto Suyoto Ismail (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Background:. Scabies is a skin disease caused by mitesSarcotes scabieivariantHominis.Transmission occurs due to personal hygiene habits consisting of bath, ablution habits, usage habits and customs dressed toiletries, sanitary environment and contact history. these conditions are found within the traditional boarding school.Methods: This case-control study carried out at mukim sntri in Pondok Pesantren Al Itqon, apopulation of as many as 66 cases of scabies and control santriyang experience sebnyak 66 healthy students. Dileti risk factors are personal hygiene habits consisting of bath, ablution habits, usage habits and customs dressed toiletries, sanitary environment and history of contact Results: personal hygiene comprising, bath appliance usage habits and customs of dressassociated with the incidence of scabies (respectively p 0.005, 0.000, 0.008) bathing habits, customs and history ablution berhubungna not contact with the incidence of scabies (respectively p 0.222, 0.379, 0.080).Conclusion: personal hygiene, which consists of the use of a custom shower and dress habitsare risk factors for the incidence of scabies with OR (2.934. 6,500. 2,734).